The Irish living kidney donor program – why potential donors do not proceed to live kidney donation?. Issue 1 (24th November 2015) - Connaughton, Dervla M.; Harmon, Grainne; Cooney, Anne; Williams, Yvonne; O'Regan, John; O'Neill, Derek; Cunningham, Phyllis; Counihan, Aileen; O'Kelly, Patrick; McHale, Siobhan; Denton, Mark; O'Seaghdha, Conall M.; et al.
Abstract: Background: Living donation is not only a method to increase access to kidney transplantation but can also offer superior outcomes. We report the experience of the living donor (LD) program in the Republic of Ireland and explore reasons why potential donors do not proceed to live donation. Methods: Retrospective cohort study of all potential donors from January 2000 to March 2014 who presented wishing to undergo donor work‐up and their subsequent outcomes. Results: A total of 956 donors for 496 recipients contacted the live kidney donation program of which 883 potential donors proceeded to the initial stage of assessment. The donor dropout rate at this stage was 64.2% (614/956 potential donors did not proceed to further evaluation). Thereafter, 269 (28.1%) donors underwent further assessment by the multidisciplinary team. In total, 93 (9.7%) donors were declined following this assessment with 176 (18.4%) donors ultimately proceeding to live kidney donation. The major reason for declining a donor was a medical contraindication (n = 63, 67.7%). In term of recipients, 54.2% (n = 269/496) had a potential donor proceed for further assessment of which 65.4% (n = 176/269) ultimately proceeding to live donation. Conclusion: Further evaluation of the declined donor group is warranted to allow for expansion of the LD program.